Lasy powiatu sieradzkiego w połowie XIX w. - Klemantowicz, Dariusz (Biuletyn Szadkowski, 2008)
The development of settlement in Poland between the 10th and 20th centuries involved gradual decrease of woodland as a result of its being turned into pastures and meadows. Changes in agriculture, population growth, and development of commerce, crafts and industry were factors which contributed to growing demand for wood as fuel and building material. In the mid-19th century forests took up 29.3% of Sieradz district’s area (as of that time). As regards the ownership structure, 88% was privately owned, the rest being governmental or municipal property.In the mid-19th century Szadek was surrounded by several forests, including the municipal forest (808.6 ha), baron von Leszern’s forest (242 ha) and private forests in Wola Przatowska (71.5 ha), Rzepiszew (774,4 ha), Willamów (438.9 ha), Wola Krokocka (304.7 ha), Prusinowice (1606 ha) and the largest complex in Wojsławice (9163 ha).